Deutsch als Fremdsprache für Erwachsene in außerschulischen Institutionen Pommerns und Westpommerns unter besonderer Berücksichtigung von Programmen und Lehrmaterialien - Bielska, Monika (Wydział Neofilologii UAM w Poznaniu, 2016)
The concept of multilingualism as well as the idea of life-long learning in the time of globalization, mobility and unlimited immigrational opportunities has been reflected not only in syllabi and textbooks used in Polish system of public education. On the market of educational services the number of continuous learning institutions is increasing. It is also noticeable that the number of language schools or language courses offered by various entities is on the increase as well as the number of adult learners. In the light of presented circumstances an attempt has been made to describe the activities of language schools from andragogic point of view considering the legal basis of their operation, organisational aspects, elements of methodological supervision as well as the development of quality and professional qualifications of German language teachers. The research was conducted at language courses for beginners in 10 language institutions in Gdynia, Lębork, Słupsk, Szczecin, Kołobrzeg and Koszalin, 8 of which belong to a private sector, one institution is supervised by The Seventh-day Adventist Church, the courses were also organised by The German Minority Association. The dissertation consists of two parts: theoretical and empirical. The theoretical part defines the notion of an adult and their typical characteristics in the process of learning (chapters I.1 and I.2) Subsequently the following notions have been defined: teaching methods (chapter 1.3), syllabi (chapter I.4), teaching materials (chapter I.5) and the role of foreign language teacher (chapter I.7). Chapters I.6 and I.7 describe the aspects of course planning as well as the possibilities of providing quality of didactic services. The empirical part presents the results of questionnaires and interviews, which mainly focus on teaching materials and implemented syllabi (chapters II.1 - II.7). The results of empirical research revealed that the main medium used during classes is the textbook and the syllabi (if they existed) were based on textbooks. Both teachers and learners were unwilling to use the latest technologies in foreign language teaching. Chapters II.8 and II.9 provide a description of prospects and challenges for still developing, as a subfield of glottodidactics, foreign language andragogic. Polish publishing market requires a detailed analysis and development of its teaching materials. Parallelly the examination of the effectiveness of teaching German at language courses for beginners is a crucial challenge. The further element requiring detailed research and reflection is foreign language teacher training in the light of contemporary job market requirements.
Keywords: nauczanie dorosłych; szkoły językowe; programy nauczania; podręczniki; adult learners; extramural institutions; teaching materials and syllabi; Erwachsenenbildung; außerschulische Einrichtungen; Lehrprogramme; Lehrwerke